2021
DOI: 10.1016/j.jamcollsurg.2020.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Increased Firearm Injury During the COVID-19 Pandemic: A Hidden Urban Burden

Abstract: BACKGROUND: Public health measures were instituted to reduce COVID-19 spread. A decrease in total emergency department volume followed, but the impact on injury is unknown. With lockdown and social distancing potentially increasing domicile discord, we hypothesized that intentional injury increased during COVID-19, driven primarily by an increase in penetrating trauma. STUDY DESIGN: A retrospective review of acute adult patient care in an urban Level I trauma center assessed injury patterns. Presenting patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
124
3
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(147 citation statements)
references
References 22 publications
19
124
3
1
Order By: Relevance
“…Although many countries and cities quickly reported a considerable and sustained decrease in trauma volume, 1 , 2 , 3 only the US reported a net decrease in blunt mechanism of injury trauma volume and a concomitant, substantial increase in firearm-related injuries in many large cities. 4 The current study by Abdallah and colleagues 5 validates these reports. The authors found a 23% relative decrease in falls from standing but a near 100% relative increase in intentional firearm-related injuries in Philadelphia, PA, before and after implementation of stay-at-home orders (SAHO) due to COVID-19.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…Although many countries and cities quickly reported a considerable and sustained decrease in trauma volume, 1 , 2 , 3 only the US reported a net decrease in blunt mechanism of injury trauma volume and a concomitant, substantial increase in firearm-related injuries in many large cities. 4 The current study by Abdallah and colleagues 5 validates these reports. The authors found a 23% relative decrease in falls from standing but a near 100% relative increase in intentional firearm-related injuries in Philadelphia, PA, before and after implementation of stay-at-home orders (SAHO) due to COVID-19.…”
supporting
confidence: 84%
“…Abdallah and colleagues 5 suggest that duration of SAHO and its resultant social and financial impact may be a large contributor to the incidence of interpersonal violence. Although this is certainly plausible, the fact that it impacted firearm-related injury only presents a key finding that should not be overlooked by policy-makers, public health officials, and disaster management personnel in anticipation of future events.…”
mentioning
confidence: 99%
“…Specifically, two studies found a significant decrease in motor vehicle collisions, 28,30 one found a significant decrease in pedestrian versus automobile accidents (but no change in motor vehicle collisions), 29 and one found an overall decrease in unintentional trauma (but no specific declines within motor vehicle collisions/pedestrian accidents). 27 In contrast, of the three studies using proportion data which found a decrease in violent trauma, one found a similar decrease in motor vehicle collisions, 20 and one found no change 34 (the third did not report these data). 21 Overall, it is possible that traumatic injuries in general increased after a brief decline at the onset of the pandemic, but that this period lasted only 1-2 months, after which other types of traumatic injuries increased, and so such data were lost: the average duration for studies reporting an increase was 52.6 days, versus 68.3 days among studies reporting a decrease, and 55.6 days among studies reporting no change.…”
Section: Methods Of Studymentioning
confidence: 94%
“…37 Of the four remaining US-based studies, ranging from 71 -181 days, three found no change in violent trauma 22,32,39 and one found increased incidence. 27 Among the nine studies that statistically examined changes in violent trauma (duration 13 -90 days), only the longest study, Salzano and colleagues, noted a decrease in violent trauma. 21 Australia based studies accounted for two records, over 60 and 61 days, and demonstrated no change (examined as a rate) and a decrease (examined as proportion) in violent trauma, respectively.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Nos collègues des États-Unis ont récemment présenté une étude de cas pertinente (suivie d'un commentaire) portant sur l'incidence de la COVID-19 sur les caractéristiques épidémiologiques locales des traumas. Plus précisément, ils ont observé une augmentation des blessures intentionnelles (particulièrement par armes à feu) alors que les visites aux urgences et les traumas accidentels étaient en baisse 2 . Notons ici que l'interprétation des auteurs demeure controversée (politiques d'isolement social sans précédent c. d'autres théories comme les ventes records d'armes à feu aux États-Unis).…”
unclassified